Clinical and brain volumetric correlates of decreased DTI-ALPS, suggestive of local glymphatic dysfunction, in iRBD - Ignacio Roura; Jèssica Pardo; Cristina Martín-Barceló; Carles Falcon; Javier Oltra; Anna Campabadal; Nuria Bargalló; Mònica Serradell; Gerard Mayà; Angelica Montini; Claustre Pont-Sunyer; Carles Gaig; et al. (npj Parkinson's Disease)
Abstract Glymphatic alterations may underlie neurodegeneration in alpha-synucleinopathies. Reduced Diffusion-Tensor Imaging ALong the Perivascular Space (DTI-ALPS), a proxy of perivascular glymphatic activity, has been scarcely studied in isolated REM sleep behaviour disorder (iRBD), a prodromal synucleinopathy stage. Furthermore, its associations with clinical symptoms and brain structural abnormalities remain unexplored. We assessed the DTI-ALPS in sixty-two patients with iRBD and twenty-three healthy controls (HC), exploring its associations with clinical symptoms, cortical thickness and brain volumetric data. iRBD patients exhibited a lower DTI-ALPS and poorer odor identification, semantic fluency and processing speed relative to HC. The DTI-ALPS positively correlated with cognitive performance, olfactory function and amygdalar, hippocampal, brainstem and diencephalic volumes, and negatively with age in iRBD. Perivascular glymphatic activity is compromised in iRBD and is associated with brain atrophy and clinical risk factors of progression to alpha-synucleinopathies, supporting the potential of the DTI-ALPS index as an early imaging neurodegeneration marker.